2022
DOI: 10.1107/s1600577521012558
|View full text |Cite
|
Sign up to set email alerts
|

Controllable sites and high-capacity immobilization of uranium in Nd2Zr2O7 pyrochlore

Abstract: As potential nuclear waste host matrices, two series of uranium-doped Nd2Zr2O7 nanoparticles were successfully synthesized using an optimized molten salt method in an air atmosphere. Our combined X-ray diffraction, Raman and X-ray absorption fine-structure (XAFS) spectroscopy studies reveal that uranium ions can precisely substitute the Nd site to form an Nd2–x U x Zr2O7+δ (0 ≤ x ≤ 0.2) system and the Zr site to form an Nd2Zr2–y U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…[41][42][43][44][45][46] Though a number of reports regarding substitution of radionuclides at the A site of the pyrochlore prevail, very insignificant work has been reported with respect to substitution at the B site. 42,47,48 In our recent report we utilized Y 2 Ti 2 O 7 as the base matrix and doped U and Ce at the Y site. 49 We observed that under reducing conditions we could incorporate 10 mol% of U.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Though a number of reports regarding substitution of radionuclides at the A site of the pyrochlore prevail, very insignificant work has been reported with respect to substitution at the B site. 42,47,48 In our recent report we utilized Y 2 Ti 2 O 7 as the base matrix and doped U and Ce at the Y site. 49 We observed that under reducing conditions we could incorporate 10 mol% of U.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Lin Wang and co-authors combined X-ray diffraction and extended X-ray absorption fine-structure (EXAFS) methods to study thorium(IV) adsorption onto multilayered titanium carbides, Ti 3 C 2 T x (Wang et al, 2021). Jian Sun and co-authors studied two series of uranium-doped Nd 2 Zr 2 O 7 pyrochlore materials as potential nuclear waste host matrices by the combination of the X-ray diffraction, Raman and EXAFS techniques (Sun et al, 2022). Using EXAFS at the U L 3 -edge and XRD, Antonia S. Yorkshire and co-authors investigated U(VI) -cement mineral interactions, relevant to under-standing the waste disposal of actinide-containing materials (Yorkshire et al, 2022).…”
mentioning
confidence: 99%
“…Key words: pyrochlore; thorium; structural evolution; chemical durability; A-site substitution; B-site substitution 高放废物(HLW)中长寿命放射性锕系核素的安 全处理处置已成为制约核工业可持续发展主要障碍 之一。 高放废物安全固化要求基材具备优异的物理、 化学、抗辐照稳定性, 其中人造岩石(Synroc)固化技 术直接将核素固化到矿相晶格位置, 是高放废物固 化处理的理想方案 [1][2][3] 。Wang 等 [4] 研究发现类萤石 结构 A 2 B 2 O 7 烧绿石陶瓷可以耐受质量分数 10%的 239 Pu 近 3000 万年辐照剂量仍能保持较好的结构稳 定性, 因此烧绿石成为锕系核素固化的潜在候选基 材 [5][6][7] 。A 2 B 2 O 7 烧绿石结构(Fd-3m)是一种缺陷的萤 石结构(AX 2 ), A、B 位为金属阳离子(过渡金属或稀 土离子), 其中 A 位占据 16c 晶格位(0, 0, 0), 与氧离 子形成八配位立方六面体结构; B 位占据 16d 晶格 位(0.5, 0.5, 0.5), 与氧离子形成六配位八面体结构。 氧离子占位为 48f(x, 0.125, 0.125)和 8a(0.125, 0.125, 0.125), 8b(0.375, 0.375, 0.375)为空位; 48f 氧离子占 位 x 具有可调性, 介于 0.3125~0.3750 之间 [8] 。 近 500 种烧绿石结构化合物被成功合成, 其中烧绿石结构 A、B 位均能实现放射性核素晶格固化, 包容+2~+5 价核素, 从而实现核素高包容量 [9] 。Belin 等 [10] 在锆 基 烧 绿 石 A 位 通 过 Am 的 晶 格 全 替 代 形 成 了 Am 2 Zr 2 O 7 固化体; Kulkarni 等 [11] 以 La 2 Zr 2 O 7 作为基 材实现了 Pu 在烧绿石 A 位晶格固化; Mandal 等 [12] 利用 Gd 2 Zr 2 O 7 作为基材实现了较小包容量 Th 在烧 绿石 A 位的替代。Kutty 等 [13] 在 Gd 2 Zr 2 O 7 的 A、B 位开展了 U 的固化研究, 烧绿石 A 位对 U 的固溶量 为 10%(原子分数); B 位固溶量较低, U 掺杂导致烧 绿石结构快速转变为萤石结构。Tang 等 [14] [17] , 能更好地包容锕系核素。锕系核 素 Th 作为重要核燃料, 随着先进重水堆(AHWR) [18] 及第四代反应堆钍基熔盐堆(TMSR) [19] [21] 。采用英国 Renishaw 公司的 [22] , 531)), 未观测到其他物相结 构衍射峰, 说明样品形成了单一烧绿石结构固化 体。烧绿石结构 A 和 B 位阳离子半径比(r A /r B )为 1.46~1.78, 超过该比例范围, 烧绿石结构会转变为 萤石结构 [9] 。烧绿石结构中八配位和六配位 Th 4+ 离 子半径分别为 0.105 和 0.094 nm, 八配位 Nd 3+ 和六 配位 Zr 4+ 离子半径分别为 0.111、0.072 nm。与 Nd 2 Zr 2 O 7 的 r A /r B 值相比(~1.54) [15] ,…”
unclassified